Control of Hepatitis B and C virus infection in chronic haemodialysis patients - Taal, Maarten Willem (Department of Medicine, 2017)
Chronic haemodialysis patients have a high prevalence of Hepatitis B and C virus infections both of which are associated with chronic liver disease and hepatocellular carcinoma Hepatitis B virus (HBV) was identified as a frequent cause of hepatitis during the early years of chronic haemodialysis therapy and strict adherence to infection control measures alone proved inadequate to control the transmission of infection between patients. A policy of regular screening of all patients and blood donations for hepatitis B surface antigen together with isolation of positive patients to separate dialysis units resulted in a significant decline in the incidence of new infections. Hepatitis B vaccination provided an important new means of protection. Despite the finding that haemodialysis patients did not respond to the vaccine as well as normal adults, randomized controlled trials showed significant protection in units with a previously high incidence of infection. Studies have identified both monocyte dysfunction and B cell inhibition by elevated levels of parathyroid hormone (PTH) as possible mechanisms for the reduced response in dialysis patients. Other factors which have been associated with this poor response include increased age, male gender, specific human leukocyte antigens, shorter time on a dialysis programme and poor nutritional status. One study has shown an increased response in patients receiving recombinant human erythropoietin and. there is in vitro evidence that nifedipine improves B cell proliferation in dialysis patients with hyperparathyroidism. Hepatitis C virus (HCV) infection in haemodialysis patients has been associated with blood transfusions in many studies. However, evidence exists that transmission between patients also occurs. There is disagreement as to what measures are necessary to prevent possible nosocomial spread. Some authors recommend isolation of HCV -infected patients to separate dialysis machines or units. There is also concern over the potential of dialyzer reuse to transmit the virus. A protocol for surveillance 0f hepatitis B and C infections was established in the dialysis unit at Groote Schuur Hospital while HCV positive patients were not isolated and reuse of dialyzers was continued for all patients. HBV -infected patients are dialyzed in a separate unit and their dialyzers are not reused. A trial of hepatitis B vaccination of all antibody negative patients was undertaken using four doses of a plasma-derived vaccine given intramuscularly at month 0,1 ,2 and 4.